2021
DOI: 10.3390/microorganisms9020343
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Pathogens on Inanimate Surfaces: A Narrative Review

Abstract: For the prevention of infectious diseases, knowledge about transmission routes is essential. In addition to respiratory, fecal–oral, and sexual transmission, the transfer of pathogens via surfaces plays a vital role for human pathogenic infections—especially nosocomial pathogens. Therefore, information about the survival of pathogens on surfaces can have direct implications on clinical measures, including hygiene guidelines and disinfection strategies. In this review, we reviewed the existing literature regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 207 publications
2
65
0
4
Order By: Relevance
“…Furthermore, many other viruses, (i.e. Adenoviruses, Rotaviruses) are stable in the environment and exhibit high infectivity and, thus, could possibly be transferred by banknotes and coins [25]. In agreement with previous reports we found that high titers of SARS-CoV-2 and its surrogate BCoV, after an initial loss of infectivity, remained infectious for days under laboratory conditions on banknotes and coins (Table 1, Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, many other viruses, (i.e. Adenoviruses, Rotaviruses) are stable in the environment and exhibit high infectivity and, thus, could possibly be transferred by banknotes and coins [25]. In agreement with previous reports we found that high titers of SARS-CoV-2 and its surrogate BCoV, after an initial loss of infectivity, remained infectious for days under laboratory conditions on banknotes and coins (Table 1, Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that RNA of human coronaviruses HCoV (OC43, 229E, HKU1, NL63), as well as MERS-CoV and SARS-CoV RNA may be detected on inanimate surfaces from just a few hours to a few days ( Kampf et al, 2020 ). Recent reports indicate that SARS-CoV-2 RNA can be detected in the air for up to 3 h after aerosolization ( Wißmann et al, 2021 ). Additional experimental efforts on surface stability of SARS-CoV-2 made in laboratory conditions show that SARS-CoV-2 is able to remain infectious for up to 24 h on cardboard surfaces, and for up to three days on plastic and stainless steel surfaces ( van Doremalen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hospital environment plays a very important role in the colonization and transmission of opportunistic pathogens. Moreover, the microorganisms responsible for hospital-acquired infections can survive for days, weeks, or even months on hospital surfaces [ 21 , 22 ]. For this reason, it is necessary to carry out microbiological monitoring of the hospital environment to find out the strains circulating in this environment.…”
Section: Discussionmentioning
confidence: 99%